2021
DOI: 10.3390/cancers13102314
|View full text |Cite
|
Sign up to set email alerts
|

Orai3-Mediates Cisplatin-Resistance in Non-Small Cell Lung Cancer Cells by Enriching Cancer Stem Cell Population through PI3K/AKT Pathway

Abstract: The development of the resistance to platinum salts is a major obstacle in the treatment of non-small cell lung cancer (NSCLC). Among the reasons underlying this resistance is the enrichment of cancer stem cells (CSCs) populations. Several studies have reported the involvement of calcium channels in chemoresistance. The Orai3 channel is overexpressed and constitutes a predictive marker of metastasis in NSCLC tumors. Here, we investigated its role in CSCs populations induced by Cisplatin (CDDP) in two NSCLC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Guzzi et al found that in mammalian stem cells, post-transcriptional RNA modification affected the biogenesis and function of tRFs [ 43 ]. PTEN/PI3K/Akt pathway is related to CSCs in various cancers [ 44 – 46 ]. Dubrovska et al found that the PTEN/PI3K/Akt pathway was closely related to prostate CSCs and PI3K might be an effective therapeutic target of prostate cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guzzi et al found that in mammalian stem cells, post-transcriptional RNA modification affected the biogenesis and function of tRFs [ 43 ]. PTEN/PI3K/Akt pathway is related to CSCs in various cancers [ 44 – 46 ]. Dubrovska et al found that the PTEN/PI3K/Akt pathway was closely related to prostate CSCs and PI3K might be an effective therapeutic target of prostate cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dubrovska et al found that the PTEN/PI3K/Akt pathway was closely related to prostate CSCs and PI3K might be an effective therapeutic target of prostate cancer [ 45 ]. In non-small cell lung cancer (NSCLC), PI3K/AKT pathway plays a great role in the enrichment of CSCs, thereby promoting the occurrence and development of NSCLC [ 46 ]. And some small RNAs such as miR-873 inhibits the proliferation and differentiation of pancreatic CSCs mediated through PI3K/AKT signaling pathway [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that Orai3 induces cisplatin resistance in NSCLC cells by enriching the population of cancer stem cells [ 51 ]. Unlike Orai1, Orai3 expression is significantly enhanced in bronchial biopsies after treatment with cisplatin, which shifts the Orai1:Orai3 expression ratio in favor of Orai3, enhances SOCE, and is associated with the expression of cancer stem cells markers, Nanog and SOX-2, most likely mediated by a mechanism dependent on the activation of the PI3K/AKT pathway [ 51 ].…”
Section: Orai3 In Lung Cancermentioning
confidence: 99%
“…A recent study has reported that Orai3 induces cisplatin resistance in NSCLC cells by enriching the population of cancer stem cells [ 51 ]. Unlike Orai1, Orai3 expression is significantly enhanced in bronchial biopsies after treatment with cisplatin, which shifts the Orai1:Orai3 expression ratio in favor of Orai3, enhances SOCE, and is associated with the expression of cancer stem cells markers, Nanog and SOX-2, most likely mediated by a mechanism dependent on the activation of the PI3K/AKT pathway [ 51 ]. Interestingly, this study also reveals that the activation of the PI3K/AKT pathway is essential for the increase in Orai3 expression after treatment with cisplatin [ 51 ], which suggest a positive feedback mechanism in the regulation of Orai3 expression and PI3K/AKT activation upon treatment with cisplatin and reveals that Orai3 might be a useful target to monitor the lung cancer outcome upon the treatment with chemotherapeutic drugs.…”
Section: Orai3 In Lung Cancermentioning
confidence: 99%
“…It is well reported that 2APB in the same concentration range of 30-50µM blocks Orai1 and activates Orai3 channels [36][37][38][39]. In past, several groups have used 2APB (50µM) to demonstrate Orai3 activation as a functional SOCE channel in breast and lung cancers [20,23,24,40,41]. Therefore, in order to examine the functionality of Orai3 as a SOCE channel in pancreatic cells, we used 2APB (50µM) in our live cell Ca 2+ imaging experiments.…”
Section: Orai3 Is Expressed In "Normal" As Well As Cancerous Pancreatic Cell Lines and Forms A Functional Ca 2+ Influx Channelmentioning
confidence: 99%